Filmy dla muzyki. Edgar Varèse i Bill Viola - Mungen, Anno (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2009)
Films for Music. Edgard Varèse and Bill Viola Anno Mungen focuses on “films made for music” and on the rare phenomenon of ‘music depicted by picture’ (S. Kracauer). The narration about historical metamorphoses of varied forms of coexistence between music and picture is accompanied by a reflection on the laws of audiovisual perception. The main examples are discussed, these concentrating on the artistic ideas of Walt Disney’s animated film Fantasia and – first of all – on Edgard Varèse’s bold ideal of spatial music, attained post mortem in Bill Viola’s Déserts (1994). After a detailed analysis of Viola’s film the author admits that the movie pictures deduced from music are able to render the latter its own substantial visual power.